Angiotensin II type 2 receptor signaling affects dopamine levels in the brain and prevents binge eating disorder. (December 2015) - Nakaoka, Hirotomo; Mogi, Masaki; Kan-no, Harumi; Tsukuda, Kana; Ohshima, Kousei; Wang, Xiao-Li; Chisaka, Toshiyuki; Bai, Hui-Yu; Shan, Bao-Shuai; Kukida, Masayoshi; Iwanami, Jun; Horiuchi, Masatsugu
Introduction: Binge eating disorder (BED) is associated with dopaminergic activation as food reward, resulting in metabolism-related disorders. Stimulation of angiotensin type 2 (AT2 ) receptor is reported to inhibit dopamine synthesis. We investigated the possible roles of AT2 receptor-mediated dopamine regulation in the pathogenesis of BED. Materials and methods: Male C57BL/6 mice, type 2 diabetic (KKAy) mice and AT2 receptor-null (AT2 KO) mice at eight weeks old were treated with AT2 receptor agonist, compound 21 (C21) or saline for two weeks. Mice were subjected to fasting for two days followed by re-feeding for seven days. Results: Treatment with C21 attenuated the rebound proportion of body weight, food intake and water intake in KKAy mice, but not in C57BL/6 and AT2 KO mice. Dopamine concentration in the striatum was further increased by fasting in KKAy and AT2 KO mice. Administration of C21 significantly attenuated this fasting-induced increase in dopamine level only in KKAy mice. Dopamine receptor D1, D2 expression in the substantia nigra were markedly lower in KKAy mice compared with C57BL/6 mice, while administration of C21 increased their expression in KKAy mice. Conclusions: Our study suggests that AT2 receptor stimulation may be a new therapeutic approach to improve eating disorder associated with dopamine resistance.